Autologous Tenocyte Injection for the Treatment of Chronic Recalcitrant Gluteal Tendinopathy: A Prospective Pilot Study. Issue 2 (21st February 2017) - Bucher, Thomas A.; Ebert, Jay R.; Smith, Anne; Breidahl, William; Fallon, Michael; Wang, Tao; Zheng, Ming-Hao; Janes, Gregory C.
Background: Gluteal tendinopathy is a common cause of lateral hip pain, and existing conservative treatment modalities demonstrate high symptom recurrence rates. Autologous tenocyte injection (ATI) is a promising cell therapy that may be useful for the treatment of gluteal tendinopathy. Purpose: To investigate the safety and effectiveness of ATI, specifically in patients with chronic recalcitrant gluteal tendinopathy. Study Design: Case series; Level of evidence, 4. Methods: Twelve female patients with a clinical and radiological diagnosis of gluteal tendinopathy were recruited. Patients demonstrated a mean duration of symptoms of 33 months (range, 6-144 months), had undergone a mean 3.2 prior corticosteroid injections (range, 2-5), and had failed to respond to existing conservative treatments including physiotherapy and injections. In an initial procedure, tendon cells were harvested from a needle biopsy of the patella tendon and propagated in a certified Good Manufacturing Practice (GMP) laboratory. In a secondary procedure, a single injection of 2 mL autologous tenocytes (2-5 × 10 6 cells/mL) suspended in patient serum was injected into the site of the pathological gluteal tendons under ultrasound guidance. Patients were assessed pre- and postinjection (3, 6, 12, and 24 months) using the Oxford Hip Score (OHS), a visual analog pain scale (VAS), the Short Form–36 (SF-36), and a satisfaction scale. Magnetic resonance imaging (MRI) was undertaken at 8.7 months (range, 6-12 months) postinjection. Results: Molecular characterization of autologous tendon cells showed a profile of growth factor production in all cases, including platelet-derived growth factor α, fibroblast growth factor β, and transforming growth factor β. The OHS (mean, 24.0 preinjection to 38.9 at 12 months [14.9-point improvement]; 95% CI, 10.6-19.2; P < .001), VAS (mean, 7.2 preinjection to 3.1 at 12 months [4.1-point improvement]; 95% CI, 2.6-5.6; P < .001), and SF-36 (mean, 28.1 preinjection to 43.3 at 12 months [15.2-point improvement]; 95% CI, 9.8-20.5; P < .001) significantly improved to 12 months postinjection, sustained to 24 months. Eight patients were satisfied with their outcomes. Significant MRI-based improvement could not be demonstrated in the majority of cases. Conclusion: ATI for gluteal tendinopathy is safe, with improved and sustained clinical outcomes to 24 months.